Perlindungan Hukum terhadap Anak dalam Terjadinya Perceraian - Gede Andi Wiradharma; I Nyoman Putu Budiartha; I Ketut Sukadana (Warmadewa Press, 2020)
Marriage is a thing that unites two individuals into one through a religious and legal ceremony. After the wedding ceremony takes place, the two individuals are married-couple. In undergoing marriage, a lot of things must be passed, so the husband and wife will have differences of opinion. The differences of opinion sometimes cause husband and wife to experience conflict which will usually lead to a fight that often ends to divorce. This research was conducted with the aim of describing how the regulation of child custody rights according to the law in Indonesia and how the legal protection of children's rights due to divorce. This research was designed using a normative legal research method. The results of this study showed that the regulation of child custody according to the law in Indonesia is regulated in Law Number 35 of 2014 concerning Child Protection and also mentions children's rights and obligations. In this law, child protection takes precedence. In addition, legal protection for children's rights due to divorce is also guaranteed where children are still entitled to receive rights from their parents such as getting an education, a decent place to live, feel secure, and get health insurance.